Bianchi Type I Cosmological Model with Viscous Fluid in the Framework of VSL Theory - Ghogre, A. S.; Khadekar, G. S.; Raut, Deepti (Communications in Mathematics and Applications, 2021)
The Bianchi type I cosmological model in the framework of Variable Speed of Light (VSL) theory is investigated, by taking into account the effect due to viscosity, considering \(\overline{p}= p-3ζ H\) where \(ζ = ζ_0 ρ H^{-1}\). The Einstein field equations are solved for variable \(G\), \(c\) and \(Λ\) in which \(G\), \(c\), \(Λ\) and shear parameter \(σ^{2}\), all are coupled. It is shown that the viscosity term exhibits the influence on the form of solutions, in the framework of varying speed of light theory.
Keywords: VSL theory; Viscous fluid; Dark energy